2019
DOI: 10.1021/acsphotonics.9b01542
|View full text |Cite
|
Sign up to set email alerts
|

Potential of Colloidal Quantum Dot Based Solar Cells for Near-Infrared Active Detection

Abstract: Nanocrystal-based solar cell technologies currently have two materials competing for the highest performances: PbS and perovskites. These latter benefit from a defect-tolerant electronic structure, while PbS benefits from a mature diode fabrication technique and from its near-infrared absorption. Here we choose to revisit the potential of these PbS photodiodes for near-infrared detection and more precisely for active imaging. This mode of detection combines an eye invisible source with a detector. Such detecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 40 publications
0
22
0
Order By: Relevance
“…Here, ITO stands for tin-doped indium oxide used as a transparent conductive contact, while ETL means electron transport layer and is generally based on either ZnO 10 or TiO 2 . 11 This diode stack achieves high internal quantum efficiency that suggests optimal charge separation and band alignment. This hypothesis was further supported by later uses of this structure for LED design.…”
Section: Introductionmentioning
confidence: 99%
“…Here, ITO stands for tin-doped indium oxide used as a transparent conductive contact, while ETL means electron transport layer and is generally based on either ZnO 10 or TiO 2 . 11 This diode stack achieves high internal quantum efficiency that suggests optimal charge separation and band alignment. This hypothesis was further supported by later uses of this structure for LED design.…”
Section: Introductionmentioning
confidence: 99%
“…13,14 These measurements provided a strategy to tune the carrier density in narrow band gap nanocrystals through ligand engineering. [15][16][17][18][19] From the photonic point of view, the diode structure also enables multi passes 20 of the light within the absorbing film. This also facilitates the realization of higher performance devices, with respect to planar photoconductive devices.…”
Section: Introductionmentioning
confidence: 99%
“…This post-synthetic surface engineering leads to high carrier mobility (4×10 -2 cm 2 V -1 s -1 ) and improved device power conversion efficiency. 2) In 2014, Chuang et al [56] showed different ligands can be gained from the development and characterization of PbS nanocrystals and devices will facilitate their use for example in photodiode applications [164,165] or can be applied to the development of other nanocrystal chemistries for solar cells, such as leadhalide perovskites as well as non-toxic, lead-free nanocrystals such as AgBiS 2 , [166] Cu 2 S, [167] or Cu 3 BiS 3 nanocrystals. [168]…”
Section: Outlook: Realizing Nanocrystal Devicesmentioning
confidence: 99%